Peningkatan Hasil Belajar Matematika Siswa Kelas V SD Inpres Batua II Bertingkat Makassar Melalui Penerapan Pembelajaran Kooperatif Tipe Numbered Head Together - Ari Wibowo (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2019)
This research is classroom action research which aims to determine whether the application of Numbered Head Together type of cooperative learning can improve the mathematics learning outcomes of fifth grade students of Makassar-level Elementary Inpres Batua II. The subject of this study was the fifth grade students of SD Makassar Inpres Batua II Bertingkat. Data was collected by using test results of learning and observation. The results showed that the average score of students in the first cycle was 54.16 with a standard deviation of 14.76. while in Cycle II the average score is 69.80 with a standard deviation of 11.06. This shows that students have achieved classical learning outcomes.